Molecular Characteristics of Regional Chromoblastomycosis in Guangdong, China: Epidemiological, Clinical, Antifungal Susceptibility, and Serum Cytokine Profiles of 45 Cases - Liu, Hongfang; Sun, Jiufeng; Li, Minying; Cai, Wenying; Chen, Yangxia; Liu, Yinghui; Huang, Huan; Xie, Zhenmou; Zeng, Weiying; Xi, Liyan (Frontiers in Cellular and Infection Microbiology, 2022)
Chromoblastomycosis (CBM) is a chronic disease caused by several species of dematiaceous fungi. In this study, a regional collection of 45 CBM cases were conducted in Guangdong, China, a hyper-endemic area of CBM. Epidemiology findings indicated the mean age of cases was 61.38±11.20 years, long duration ranged from 3 months to 30 years, and gender ratio of male versus female was 4.6:1. Thirteen cases (29%) declared underlying diseases. Verrucous form was the most common clinical manifestation (n=19, 42%). Forty-five corresponding clinical strains were isolated, and 28 of them (62%) were identified as F. monophora, the remained 17 (38%) were identified as F. nubica through ITS rDNA sequence analysis. Antifungal susceptibility tests in vitro showed low MICs in azoles (PCZ 0.015-0.25μg/mL, VCZ 0.015-0.5μg/mL, ITZ 0.03-0.5μg/mL) and TRB (0.015-1μg/mL). Itraconazole combined with terbinafine was the mainly therapeutic strategy used for 31 of 45 cases, and 68% (n=21) of them improved or cured. Cytokine profile assays indicated up-regulation of IL-4, IL-7, IL-15, IL-11 and IL-17, while down-regulation of IL-1RA, MIP-1b, IL-8, IL-16 compare to healthy donors (p<0.05). The abnormal cytokine profiles indicate impaired immune response to eliminate fungus in CBM cases, which probably contributed to chronic duration of this disease. In conclusion, we investigated the molecular epidemiological, clinical and laboratory characteristics of CBM in Guangdong, China, which may assistance further clinical therapy, as well as fundamental pathogenesis study of CBM.